Organizational behavior - Robbins, Stephen P.; Judge, Timothy A. (Delhi : Pearson, 2006)
Business
Keywords: Organizational Behavior; Individual behavior; Job satisfaction; Personality and emotion; Motivation; Organizational culture; Human resource policies; Communication; Organizational change; Stress management; Power and Politics; Leadership; Conflict and negotiation; Diversity in organizations